Transcriptome and nutritional composition analysis of stacked transgenic maize with insect resistance and herbicide tolerance - Xiaoxing Yu; Hongyu Gao; Pengfei Wang (GM Crops & Food)
The safety assessment of stacked transgenic crops is essential for their commercial cultivation. A crucial element of safety assessment is the nutritional evaluation of transgenic crops. Currently, profiling methods like transcriptome are employed as supplemental analytical tools to find the unintended effects of transgenic crops. In this study, stacked transgenic maize ZDRF8×nCX-1 was produced by crossing of two transgenic maize events ZDRF8 and nCX-1. This stacked transgenic maize expresses five genes: cry1Ab, cry2Ab and g10evo-epsps (from ZDRF8), as well as cp4 epsps and P450-N-Z1 (from nCX-1). Molecular analysis showed that the insertion sites of target genes were not changed during stack breeding, and the target genes are effectively expressed at both RNA and protein levels in ZDRF8×nCX-1. Target trait analysis showed that ZDRF8×nCX-1 exhibits tolerant to glyphosate, flazasulfuron and MCPA, and is resistant to damage by corn borers. Transcriptome analysis revealed that gene-stacked maize ZDRF8×nCX-1 did not significantly alter transcriptome profiles compared to the transgenic maize events ZDRF8 and nCX-1. Nutritional composition analysis showed that the grain profile of ZDRF8×nCX-1 was substantially equivalent to that of the non-transgenic counterpart. These results suggest that hybrid stacking does not cause significantly unintended effects beyond providing the intended beneficial traits.